Hubungan asupan enegi dan protein dengan status gizi berdasarkan %LILA menurut umur pada pasien Chronic Kidney Disease on Hemodialisis di RSUD Dr. Saiful Anwar Malang - Riani, Atika Puspa (Jurnal Labora Medika, 2019)
Chronic Kidney Disease (CKD) is decreasing kidney function to maintain metabolism balance, fluid, and electrolytes caused by glomerular inflamation, urinary tract infectons, and drug consumption. The severity of CKD at end stage of dialysis need to be done by removing the remaining water and improving the balance of water, electrolytes and protein. CKD patients are at risk to be malnutrition which caused by inadequate intake due to gastrointestinal disorders, decreased appetite due to nausea, vomiting, psychological factors and losses of protein in hemodialysis process. This study aims to determine the relationship between energy and protein intake with nutritional status based on MUAC for Age in patients with CKD on Hemodialysis in Dr. RSUD. Saiful Anwar Malang. This study used observational research using cross sectional design which involved by 31 CKD patients with hemodialysis therapy in the inpatient room of RSUD Dr. Saiful Anwar Malang by using purposive sampling. Nutritional status data based on MUAC for age was obtained through measurement of the patient's MUAC by metlin used. Energy and protein intake were obtained by interviewing Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Univariate results showed that the nutritional status of respondents was malnutrition (54.8%) and normal (45.2%). Most of the energy and protein intake were in adequate category (48.8% and 37.2%). Bivariate test results which used Spearman showed there was significant positive correlation between energy and protein intake and nutritional status based on MUAC for age (p = 0.00; r = 0.787 and r= 0.64), so the more adequate intake, the better of nutritional status.